دور القيادة التحويلية في تطبيق اليات الحوكمة الإدارية - أ.نورالدين رحومة الديب; أ. عبد الرزاق محمد ابورزيزة; أ. منير أحمد المخرم (Aljameai, 2025)
المستخلص: تناولت هذه الدراسة دور القيادة التحويلية في تطبيق اليات الحوكمة الإدارية دراسة تطبيقية على جهاز تنمية وتطوير المراكز الإدارية طرابلس (السواني)، وتمكن مشكلة الدراسة في وجود تحديات متزايدة تواجهها المؤسسات، في تطبيق مبادئ الحوكمة الإدارية بشكل فعّال، وذلك لأسباب عديدة، منها غياب القيادة الفعّالة القادرة على تحفيز وتوجيه الجهود نحو تحقيق أهداف الحوكمة، ويتكون مجتمع الدراسة من جميع الموظفين بجهاز تنمية وتطوير المراكز الإدارية فرع طرابلس (السواني) والبالغ عددهم (54) موظف، ونظرا لصغر حجم مجتمع الدراسة تم استخدام أسلوب المسح الشامل. وتهدف الدراسة التعرف على العلاقة التي تربط القيادة التحويلية بأليات الحوكمة الإدارية.، تم استخدام الاستبانة كأداة لجمع البيانات، واتبعت الدراسة المنهج الوصفي والتحليلي، لتحليل البيانات. وتوصلت الدراسة إلى عدة نتائج، منها: وجود علاقة طردية متوسطة بين تطبيق القيادة التحويلية وتطبيق مبادي الحوكمة الإدارية في إدارة جهاز تنمية وتطوير المراكز الإدارية. وأوصت الدراسة بضرورة، ربط منهجية القيادة التحويلية كعمل وعلاقتها بالحوكمة الإدارية، زيادة نشر مفهوم القيادة التحويلية كأسلوب قيادي حديث وفعال في الجهاز.Abstract:This study examines the role of transformational leadership in implementing administrative governance mechanisms. This study is an empirical study of the Administrative Centers Development and Development Authority, Tripoli (Al-Suwani). The study's problem lies in the increasing challenges facing institutions in effectively implementing administrative governance principles. This is due to several reasons, including the lack of effective leadership capable of motivating and directing efforts toward achieving governance objectives. The study population consists of all employees of the Administrative Centers Development and Development Authority, Tripoli (Al-Suwani) branch, totaling (54) employees. Due to the small size of the study population, a comprehensive survey method was used. The study aims to identify the relationship between transformational leadership and administrative governance mechanisms. A questionnaire was used as a data collection tool, and the study followed a descriptive and analytical approach to analyze the data. The study reached several results, including: the presence of a moderate positive relationship between the application of transformational leadership and the application of administrative governance principles in the management of the Administrative Centers Development and Development Authority. The study recommended the necessity of linking the transformational leadership methodology as a process and its relationship with administrative governance, and increasing the dissemination of the concept of transformational leadership as a modern and effective leadership style within the Authority.